Independent Modal Variable Structure Fuzzy Active Vibration Control of Cylindrical Thin Shells Laminated with Photostrictive Actuators. (2013) - He, R.B.; Zheng, S.J.; Wang, H.T.
Abstract : Photostrictive actuator, which can produce photodeformation strains under the activation of ultraviolet lights, is a new promising non-contact photoactuation technique for active vibration control of flexible structures. Generally, the membrane control action plays a major role in vibration control of flexible thin shell structures. However, it is unfortunate that the existing photostrictive actuator configuration can not induce negative membrane control forces. In this paper, a novel multi-layer actuator configuration is first presented to remedy this deficiency, followed by presenting the photostrictive/shell coupling equations of thin cylindrical shells laminated with the proposed multi-layer actuator configuration. Moreover, considering the time-variant and nonlinear dynamic characteristics of photostrictive actuator, variable structure self-adjusting parameter fuzzy active controller is explored to overcome disadvantages of conventional control schemes, in which off-line fuzzy control table is adopted. The optimal switching surface is derived to increase the range of sliding mode to facilitate vibration suppression. A continuous function is used to replace the sign function for reducing the variable structure control chattering. Finally, two case studies are carried out to evaluate the effectiveness of the proposed actuator configuration and the control scheme. Numerical simulation results demonstrate that the proposed actuator configuration is effective in shell actuation and control. It is also suggested that the proposed control strategy could give better control responses than the proportional velocity feedback.